(untitled) (ModaPalavra e-periódico, 2022)
T-shirts have become part of important moments in fashion, revealing themselves as a “flag” of concepts and ways of thinking about a certain theme in society. They are relevant in political demonstrations as a way of disseminating the support or rejection of a significant issue that may affect the community, some specific groups or a country. This research aims to analyze the design of t-shirts as a vehicle for messages in political demonstrations. Therefore, a case study of t-shirts in political demonstrations in Colombia and Brazil from 2012 to 2016 was carried out. An analysis proposal on the use of t-shirts is presented and has four main aspects: typographic, use of color, symbology and speech. The results demonstrate the importance of design to influence decision making, in addition to the similarities and differences of the two cases analyzed and how the elan in the discourse helps to strengthen and transform a message, generating new forms of approach.